THE ALGORITHM OF AUTOMATIC RECOGNITION OF GEOPHYSICAL PROCESSES ANALOG RECORDS WITH THE USE OF DYNAMIC PROGRAMMING METHOD - Burtsev A.A.; Zhizhin M.N. (My University, 2000)
Since the large number of the valuable analog records of earthquakes (seismograms, magnetograms, and the like) can not be used for direct computer processing, as well as because of the short life of the conventional data carriers, such as paper and microfilms, these records need be transformed to the electronic carriers. To solve this problem, we developed an algorithm for reconstructing the self-recorder trace to its electronic view. This algorithm includes five stages, namely, (1) the quantization of the image, (2) its skeletonization, (3) the identification of linear primitives, (4) the selection and splicing of the primitives which form the recorder trace, and finally (5) the interpolation of the trajectory, and its reduction to the physical units.
Keywords: AUTOMATIC PATTERN RECOGNITION; GEOPHYSICAL PROCESSES; DYNAMIC PROGRAMMING METHOD